Cognitive Behavioral Therapy (CBT) in Reducing Symptoms of Self Injury in Adolescents with Depression Major Disorder - Kamil, Nizamuddin (Kirana Publisher (KNPub), 2024)
Self injury is the behavior of self injuring in various ways regardless of whether or not there is an intention and desire to die. Self injury behavior in adolescents can have a long-term impact on adulthood. The purpose of this study is to reduce the behavior of adolescents who injure their hands with major depressive disorder using Cognitive Behavior Therapy (CBT) techniques. To achieve this goal, CBT therapy was conducted for 3 weeks with 3 times a week. This study uses CBT theory helping clients to examine the validity of their thinking and to see how they interpret or evaluate something that happens and its effect on emotional and behavioral experiences. The subjects in this study were junior high school students. The data analysis process used visual graph techniques. The results of this study showed that CBT therapy was able to reduce self-harm behavior in adolescents with major depressive disorder.